Some aspects of syntactic development in 5-6 year old Tamil speaking children: a descriptive study - Venugopal S (Journal of All India Institute of Speech and Hearing, 1970)
In this study an attempt was made to investigate the development of some aspects of syntactic patterns in 5-6 year old children. Four children one boy and one girl in each age group whose mothertongue is Tamil and belong to middle class families residing in Mysore were selected for the study. All the four are from non Brahmin families. The age range of the children was from 4 years 8 months to 6 years 1 month. A total of 3 hours speech sample was recorded with each child at his/her home using a portable cassette tape recorder. This sample consisted of four separate 45 minutes recordings'. All the four recordings were completed within a duration of 6 days.